Response of Long Bean Vegetative Growth Due to Different Types of Mulch and Doses of Vermicompost - Ahmad Raksun; Moh. Liwa Ilhamdi; I Gde Mertha; I Wayan Merta (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Long beans are plants of the Leguminoceae family that grow on vines. Long bean growth rate is influenced by various factors. Some of the external factors that determine the growth rate of long beans are the availability of nutrients and the application of mulch on agricultural land. Research on the vegetative growth response of long bean due to different types of mulch and doses of vermicompost fertilizer has been carried out in Mertak Umbak Village, Central Lombok. This study aims to analyze: (1) the vegetative growth response of long bean due to different types of mulch, (2) the vegetative growth response of long bean due to different doses of vermicompost, (3) the effect of a combination of types of mulch and vermicompost dosage on long bean growth. Research data were analyzed using Anova. The research results show that: (1) the vermicompost treatment significantly affected the increase in total leaf and plant height, but did not have a significant effect on the length and width of long bean leaves, (2) the application of mulch had a significant effect on all observed growth parameters, the highest growth parameters were observed in the application of plastic mulch black silver, (3) the interaction of mulch type and vermicompost dosage had a significant effect on plant height but did not have a significant effect on other growth parameters.